Religious Anthropology Of The Tradition Of The Ngaben Ceremony On Human Relationship With God: Antropologi Religius - pitaloka, lola; Febriani, Riska (Jurnal Studi Agama, 2023)
This study aims look at the human relationship to God. Humans must always worship, carry out God's commands and stay away from his prohibitions. However, Indonesia also has many different cultures to convey how someone fears God. On the opposite side of the island of the gods, they have different cultural traditions from other regional traditions, when a resident dies, the Bali Hindu community has a ritual, namely that funeral pyre is believed to be ritual to perfect the body. The previous religious theory of human life, Edward B Tylor, is considered the father of anthropology. He said the origin of religion is human awareness of the soul. Answer theory and formulation the problem, research uses descriptive qualitative research methods, will later use journal literature, articles and sources from social media, will be strengthened data validation techniques which will see the relationship between theory, observation, interviews and documentation. The results of the discussion conclude that the human relationship with God can also be influenced by the environment of tradition and culture, one example is the Ngaben tradition, which emotionally and spiritually strengthens the relationship between humans and God, as well as the practice of worship. Keywords: Religious Anthropology, Ngaben, Tradition